Towards Design Guidelines for IoT Applications considering Elderly Users - Rodrigues, Sandra Souza; Fortes, Renata Pontin De Mattos; Rodrigues, Kamila Rios da Hora (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
The Internet of Things (IoT) has become a relevant topic in Human-Computer Interaction (HCI), as it has introduced a new technological paradigm capable of transforming how people experience and use technology. Despite the significant growth in the number of connected devices in IoT scenarios, not all users have the same ability to benefit from this technology. Population aging is a global phenomenon that occurs at an accelerated pace. Thus, elderly users (60+) also must be able to use technologies like IoT. In this regard, design guidelines play a crucial role. Therefore, in this paper, we have established a set of guidelines to support designers and developers in constructing IoT solutions, focusing on elderly users and considering requirements such as usability and accessibility. The guidelines were created following several steps, namely: literature review, interviews with elderly users and companies, expert evaluation steps, and conducting a proof of concept. The guidelines were subjected to cycles of evaluations and refinements that resulted in new versions of the set. The results of the evaluations showed that the current version of the guidelines (version 2.1) supports the development of IoT applications since developers, when using them, consider accessibility and usability issues more effectively for elders.